Analysis of Factors Affecting the Menstrual Cycle Among Adolescent Girls: A Scoping Review - Aningsih, Sri; Amalia, Silviatul; Safitri, Yulia Retno; Rahayu, Widya (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
Menstruation is an important indicator of women’s reproductive health and is frequently disrupted during adolescence due to physiological adaptation and multiple external factors. This study aims to identify and synthesize the determinants influencing menstrual cycle regularity among adolescent girls based on recent research evidence. A Scoping Review was conducted according to PRISMA guidelines, using articles published between 2021–2025 from PubMed, Scopus, Science Direct, and Wiley databases. Eight eligible studies were analyzed narratively under three main categories: psychological, physiological, and lifestyle factors. Findings indicate that stress is the most dominant factor associated with menstrual cycle disturbances through hypothalamic–pituitary–ovarian (HPO) axis dysfunction. Physiological factors such as high body mass index (BMI), obesity, and hormonal imbalance were significantly correlated with irregular cycles and increased risk of polycystic ovary syndrome (PCOS). Unhealthy lifestyle behaviors, including sleep duration of <6 hours, high-fat intake, and excessive physical activity, further contributed to irregularities. Poor sleep quality and unbalanced diet disrupted the circadian rhythm and hormonal regulation of the reproductive system. Overall, menstrual irregularities result from an interaction of biological, psychological, and behavioral factors, most of which are modifiable. Comprehensive reproductive health education and healthy lifestyle interventions are crucial to prevent and manage menstrual disorders. Further longitudinal studies are recommended to strengthen causal evidence among variables